Social Media, Social Support, and Mental Health of Young Adults During COVID-19 - Longest, Kaitlyn; Kang, Jin-Ae (Frontiers in Communication, 2022)
The current study examines the impact of COVID-19 on the mental health among young adults in the US, how they use social media and the social support they obtain from the online environment, and the effect on their mental health during stay-at-home orders. Our survey among 18-to-25-year-olds found that women and those uncertain of employment status due to the pandemic experienced elevated depression symptoms. The informational acquisition motive for using social media was positively associated with depression symptoms, and a higher level of online informational support contributed to increasing the symptoms. Young adults showed the lowest level of depression symptoms when they had a higher level of offline emotional support and a lower level of online informational support. Our survey stressed the importance of offline emotional support and reconfirmed that nothing can replace its value.